The Ukrainian version of the Perceived Injustice Questionnaire: A psychometric evaluation - Anna Weigelt; Jan Ilhan Kizilhan; Jan Ilhan Kizilhan (Frontiers in Psychiatry, 2024)
IntroductionPerceived injustice is increasingly recognized as a key factor influencing mental health in war survivors. This cross-sectional study aimed to evaluate the psychometric properties of the Ukrainian translation of the Perceived Injustice Questionnaire (PIQ) among individuals directly exposed to the war in Ukraine.Methods170 war-exposed Ukrainians completed the Ukrainian PIQ and measures of post-traumatic tress disorder (PCL-5), depression (PHQ-9), generalized anxiety disorder (GAD-7), and potentially traumatic life events (LEC-5). Internal consistency, factor structure, and criterion validity were assessed.ResultsWhile the factor structure of the English version could not be reproduced, indicating an issue with factor validity in the Ukrainian version, the Ukrainian PIQ demonstrated strong correlations with post-traumatic stress disorder (PTSD) symptoms (r = .71, p <.01), moderate associations with depression (r = .62, p <.01) and generalized anxiety disorder (r = .61, p <.01), and a weaker link with potentially traumatic life events (PTLEs, r = .35, p <.01). It significantly predicted PTSD, depression, and generalized anxiety disorder (GAD) symptoms beyond PTLE exposure, explaining 33% of variance in depression, 31% in GAD, and 45% in PTSD These findings provide evidence supporting the construct validity of the PIQ in terms of its relationships with mental health outcomes. The Ukrainian PIQ also demonstrated excellent overall reliability (α = .90), with factor reliabilities ranging from α = .74 to α = .81.ConclusionsThe Ukrainian version of the PIQ demonstrates promising psychometric properties and emerges as a highly significant correlate of mental health outcomes. This underscores its potential utility in clinical practice for assessing the treatment needs of Ukrainians affected by the consequences of war. Moreover, the findings highlight the importance of developing therapy modules specifically tailored to address perceived injustice. Further research is warranted to investigate the cross-cultural adaptability and comparability of the PIQ.